Phylogenomics and evolution of floral traits in the Neotropical tribe Malmeeae (Annonaceae) - Lopes, J. C.; Chatrou, L. W.; Mello-Silva, R.; Rudall, P. J.; Sajo, M. G. [UNESP] (Elsevier B.V., 2018)
Androdioecy is the rarest sexual system among plants. The majority of androdioecious species are herbaceous plants that have evolved from dioecious ancestors. Nevertheless, some woody and androdioecious plants have hermaphrodite ancestors, as in the Annonaceae, where androdioecious genera have arisen several times in different lineages. The majority of androdioecious species of Annonaceae belong to the Neotropical tribe Malmeeae. In addition to these species, Pseudoxandra spiritus-sancti was recently confirmed to be androdioecious. Here, we describe the morphology of male and bisexual flowers of Pseudoxandra spiritus-sancti, and investigate the evolution of androdioecy in Malmeeae. The phylogeny of tribe Malmeeae was reconstructed using Bayesian inference, maximum parsimony and maximum likelihood of 32 taxa, using DNA sequences of 66 molecular markers of the chloroplast genome, sequenced by next generation sequencing. The reconstruction of ancestral states was performed for characters associated with sexual systems and floral morphology. The phylogenetic analyses reconstructed three main groups in Malmeeae, (Malmea (Cremastosperma, Pseudoxandra)) sister to the rest of the tribe, and (Unonopsis (Bocageopsis, Onychopetalum)) sister to (Mosannona, Ephedranthus, Klarobelia, Oxandra, Pseudephedranthus fragrans, Pseudomalmea, Ruizodendron ovale). Hermaphroditism is plesiomorphic in the tribe, with four independent evolutions of androdieocy, which represents a synapomorphy of two grotips, one that includes three genera and 14 species, the other with a single genus of seven species. Male flowers are unisexual from inception and bisexual flowers possess staminodes and functional stamens. Pseudoxandra spiritussancti is structurally androdioecious.
Keywords: Ancestral state analysis; Androdioecy; Floral morphology; Next-generation sequencing